Regular inclusive learning environment a study based on the commonalities of inclusive factors between the special and early childhood education in Davao City - Valdez, Jovianne Angela M.; Sebastian, Myrafe L. (2016)
Social skills are important factors that can help a child succeed in all aspects of his/her life. As a child grows, so does his social awareness and skills. However, for a child with social needs, learning social skills and forging new friendships can be stressful and scary. Research tells that children learn best in natural environments with typically developing peers, broadening their competitive and social skills. The inclusion principle states that special children should be incorporated to a regular classroom regardless of their disability such as to help them grow in a normal environment and develop social interaction skills. Inclusive education provides a more stimulating environment leading to enriched growing and learning, more engaged instructional time and has greater exposure to academic activities. To determine the possibility of an Inclusive Education in Davao City, determining the extent of commonalities in terms of Inclusive Factors-Academic Curriculum, Social Skills and Learning Environment, , of both regular children and children with disabilities was done. Curriculum guides of both students were analyzed for common activities; Social Skills Checklist was answered by 105 teachers among the 1470 SPED and Kindergarten learners. School Assessment was also given to the teachers and parents so as to know the current characteristics of the learning environment of the school and lastly, Functional Behavior Assessment was done by the teachers on the selected students that showed disruptive behaviors. As a tool of analysis on the aforementioned research tools, Spearman Rho correlation was used to determine the relationship of the SPED and Kindergarteners in terms of Inclusive Factors. The research found that (1) 4 out of 6 of SPED subjects and all of the Kindergarten subjects have common activities, (2) 6 out of the 8 Environmental factors were also common, (3) Social Skills, that mainly highlights on play, understanding and compliment behaviors, were also common, (4) the stimuli that could trigger disruptive behavior/s on learners are increase in motor activity and unstructured work and lastly (5) through correlation test, it was also found that there is a strong positive relationship of the Environment characteristics and Social Skills of SPED learners while there is a moderate positive relationship for the Kindergarten learners. The results became the baseline on creating a design guideline of a new way of pedagogy by creating interactive school that does not only suit their health and academic needs but also their social skills.
Thesis (BS Architecture) -- University of the Philippines Mindanao, June 2016.